Pengaruh Jarak Pupil Terhadap Pengelihatan Stereoskopis Pada Pasien Penderita Mata Miopia Di Rumah Sakit Pertamina Bintang Amin Husada Bandar Lampung - Rahmat Syuhada; Nia Triswanti; Doni Armanda (Universitas Malahayati, 2022)
ABSTRACTRefractive disorders are one of the causes of blindness and visual impairment when doing activities. Lampung Province is in the 6th rank (0.5%) for blindness in respondents aged ≥6 years. Meanwhile, the prevalence of low vision ability at productive age (15-54 years) was 1.49% and the prevalence of blindness was 0.5%. It is known to know the effect of pupil distance on stereoscopic vision in patients with myopia at Pertamina Bintang Amin Husada Hospital, Bandar Lampung. This study is an analytics study using a cross-sectional study design. The population in this study was that patients diagnosed with myopia eye at Pertamina Bintang Amin Husada Hospital in Bandar Lampung were conducted by one of the eye specialist doctors at the related Hospital Hospital. And in the last three months at Bintang Amin Husada Hospital, there were an average of 2,441 patients diagnosed with myopia per month, a sample of 60 patients. Retrieval of data using the observation sheet. Data analysis techniques using frequency distribution. The results of the degree of myopia from 60 respondents were mild myopia by 31 respondents by a percentage (51.7%), The results of the pupil distance of 60 respondents were 62-64 mm for 30 respondents by a percentage (50%), The results of stereoscopic vision were from 60. respondents are> 200 arc seconds as many as 32 respondents with a percentage (58.3%). There is an influence between pupil distance and stereoscopic vision. In this study, a correlation coefficient of 0.623 was obtained, which means that the pupil distance greatly affects stereoscopic vision. Keywords: Pupil Distance, Stereoscopic Vision, Myopia ABSTRAKKelainan refraksi merupakan salah satu penyebab kebutaan dan hambatan penglihatan ketika beraktivitas. Provinsi Lampung menduduki peringkat ke 6 (0,5%) kebutaan pada responden umur ≥6 tahun. Sedangkan prevalensi kemampuan penglihatan rendah pada usia produktif (15-54 tahun) sebesar 1,49% dan prevalensi kebutaan sebesar 0,5%. Tujuan penelitian untuk mengetahui pengaruh jarak pupil terhadap pegelihatan setereoskopis pada pasien penderita miopia di Rumah Sakit Pertamina Bintang Amin Husada Bandar Lampung. Penelitian ini merupakan penelitian analitik dengan menggunakan desain cross sectional study, Populasi pada penelitian ini pasien terdiagnosis mata miopia di Rumah Sakit Pertamina Bintang Amin Husada Bandar Lampung yang dilakukan oleh salah satu dokter spesialis mata Rumah Sakit terkait. Dan pada tiga bulan terkakhir di Rumah Sakit Bintang Amin Husada memiliki rerata 2.441 pasien terdiagnosis myopia perbulannya, sampel sebanyak 60 pasien. Pengambilan data menggunakan lembar observasi. Teknik analisis data menggunakan distribusi frekuensi. Hasil derajat miopia dari 60 responden adalah miopia ringan sebanyak 31 responden dengan presentase (51,7%), Hasil jarak pupil dari 60 responden adalah 62-64 mm sebanyak 30 responden dengan presentase (50%), Hasil pengelihatan stereoskopis dari 60 responden adalah >200 detik busur sebanyak 32 responden dengan presentase (58,3%). Ada pengaruh antara jarak pupil dan penglihatan stereoskopis. Pada penelitian ini di dapatkan korelasi koefisien sebesar 0,623 dapat diartikan bahwa jarak pupil sangat mempengaruhi dari pada pengelihatan stereoskopis. Kata Kunci: Jarak Pupil, Pengelihatan Stereoskopis, Miopia